C-Jun-N-terminal phosphorylation regulates DNMT1 expression and genome wide methylation in gliomas - Heiland, Dieter Henrik; Ferrarese, Roberto; Claus, Rainer; Dai, Fangping; Masilamani, Anie P.; Kling, Eva; Weyerbrock, Astrid; Kling, Teresia; Nelander, Sven; Carro, Maria S. (Oncotarget, 2017)
High-grade gliomas (HGG) are the most common brain tumors, with an average survival time of 14 months. A glioma-CpG island methylator phenotype (G-CIMP), associated with better clinical outcome, has been described in low and high-grade gliomas. Mutation of IDH1 is known to drive the G-CIMP status. In some cases, however, the hypermethylation phenotype is independent of IDH1 mutation, suggesting the involvement of other mechanisms. Here, we demonstrate that DNMT1 expression is higher in low-grade gliomas compared to glioblastomas and correlates with phosphorylated c-Jun. We show that phospho-c-Jun binds to the DNMT1 promoter and causes DNA hypermethylation. Phospho-c-Jun activation by Anisomycin treatment in primary glioblastoma-derived cells attenuates the aggressive features of mesenchymal glioblastomas and leads to promoter methylation and downregulation of key mesenchymal genes (CD44, MMP9 and CHI3L1). Our findings suggest that phospho-c-Jun activates an important regulatory mechanism to control DNMT1 expression and regulate global DNA methylation in Glioblastoma.
CRIS-Team Scopus Importer:2024-03-07
Keywords: DNMT1; G-CIMP; Glioblastoma; Mesenchymal; P-c-Jun